Development of Land–Sea–Air–Space Integrated Information Network - Xu Xiaofan, Wang Niwei, Gao Yingyuan, Lu Zhou, Wang Chunting, Lu Jun (《中国工程科学》杂志社, 2021)
The land–sea–air–space integrated information network is capable of providing globally accessible, safe, and reliable information services for land-, sea-, space-, and air-based users; it is an important infrastructure for China to maintain independence in the field and to become a cyberpower. This study uses literature research and expert consultation as the main research methods to summarize the development requirements of the land–sea–air–space integrated information network. After a detailed study on typical domestic and foreign systems, the major weaknesses of China’s land–sea–air–space integrated information network are summarized. Moreover, an integrated information network architecture and development routes are proposed. Specifically, we suggest that China should focus on the deep integration in terms of network architecture, technical system, and application services; integrate the communication, navigation, and remote sensing systems; promote technical independence and industrial upgrade of space-based networks; and strengthen its system security protection capabilities.